The assessment of fulfilment of educational and informational needs of women who start breast cancer treatment - Kołłątaj, Witold; Karwat, Irena Dorota; Kołłątaj, Barbara (Polish Journal of Public Health, 2010)
Introduction. Breast cancer is the most common malignant cancer affecting women in Poland. The diagnosis: ‘breast cancer’ – suddenly changes the perception of the entire surrounding world, creates serious dilemmas and brings to mind many important questions. Questions left without answers may create fear which, in turn, may cause rejection of treatment proposals, ceasing current treatment or looking for alternative methods of therapy. Aim. The aim was to assess educational and informational needs of women who started treatment for breast cancer. Material and method. The tested group consisted of 116 women – the members of the Lublin Amazon Women Association, aged 35-82, with breast cancer diagnosed within 16 years (1992-2008). The retrospective method was used. The original inquiry questionnaire was applied. Results. At the beginning of the therapy, when the diagno-sis was settled, almost all the tested women, presented moderate or really unsatisfying knowledge concerning breast cancers. All of them needed to broaden their knowledge and lots of them did not have sufficient information about the disease. More than 50% of women stated that their needs concerning information about the causes of the disease and details of treatment were not fulfilled. More than 1/3 of the polled women were dissatisfied with limited access to brochures addressed to patients with breast cancer; more than half of them – with consultations with oncologists. No less than 40% of the polled women were dissatisfied with the results of consultations with physiotherapists, dieticians and psychologists. The polled women highly appraised priests’ care (only 23% women expressed negative opinions). Conclusions. Women who start treatment for breast cancer are a large group of people with special educational, medical and psychological needs which are not fulfilled satisfactorily. Some of these needs may be fulfilled by applying better educational and information procedures. It seems advisable to establish a new medical specialty minder-educator – to take better care of patients with malignant diseases.